Comparative secretome analysis of Indian wheat leaf rust pathogen Puccinia triticina - JASWAL, RAJDEEP; DUBEY, HIMANSHU; KIRAN, KANTI; SINGH, PANKAJ KUMAR; RAWAL, HUKAM C; BHARDWAJ, SUBHASH C; PRASAD, PRAMOD; GUPTA, NAVEEN; SHARMA, T R (The Indian Journal of Agricultural Sciences, 2019)
The secretome of two races, 77-5 and 106 of wheat leaf rust pathogen Puccinia triticina with known virulence and avirulent trait, respectively were analyzed in this study. The secretome analysis revealed 546 putative secretory proteins (PSPs) present in the race 77-5, and 481 PSPs in race 106. Race-specific PSPs analysis also showed that race 77-5 had higher number of PSPs (19.72%) in comparison to race 106. Various other gene families like pathogenicity and virulence factor were also expanded in higher number in the race 77-5 and few of them having multiple domains which are known for pathogenicity, were exclusively present in this virulent race. The candidate secretory effector proteins (CSEP) analysis also showed that the virulent race contained 8.98% higher CSEP proteins compared to the avirulent race 106. The results suggest that these genes are playing important roles in their respective race-specific manner. Surprisingly the carbohydrate metabolism-related enzymes were found 5.26% higher in the avirulent race in comparison to the virulent one, and few of them have shown race specificity. The in-silico expression analysis of the selected candidate’s genes also revealed their role in the pathogenesis process. The three dimensional (3D) structure predictions were performed for few of the candidate genes that were highly expressed. In this comparative secretome analysis, our findings provide a baseline for the characterization of effectors and avirulence factors in different races of P. triticina.